(untitled) (Bangladesh Journal of Pharmacology, 2015)
The purpose of this study is to test the effects of Dietary Approaches to Stop Hypertension (DASH) diet plan on pregnancy outcomes patients with gestational diabetes mellitus. This randomized controlled clinical trial was performed among 33 women diagnosed with gestational diabetes. These patients were randomly distributed to the control group (n = 16) or DASH diet group (n = 17) for 4 weeks. Whereas 47.1% of women in the DASH diet needed to have a cesarean section, this percentage of mean gestational age in control diet was 81.3% (p<0.01). Approximately 23.5% of women in the DASH diet and 75% of women in control diet needed to commence insulin therapy after intervention (p<0.01). In conclusion, the effect of DASH diet improved pregnancy outcomes patients with gestational diabetes.